2015
DOI: 10.1186/s13075-014-0514-0
|View full text |Cite
|
Sign up to set email alerts
|

A genetic study on C5-TRAF1 and progression of joint damage in rheumatoid arthritis

Abstract: IntroductionThe severity of joint damage progression in rheumatoid arthritis (RA) is heritable. Several genetic variants have been identified, but together explain only part of the total genetic effect. Variants in Interleukin-6 (IL-6), Interleukin-10 (IL-10), C5-TRAF1, and Fc-receptor-like-3 (FCRL3) have been described to associate with radiographic progression, but results of different studies were incongruent. We aimed to clarify associations of these variants with radiographic progression by evaluating six… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
108
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(112 citation statements)
references
References 39 publications
4
108
0
Order By: Relevance
“…Other serum markers for eOA detection have been suggested - disintegrin and metalloproteinase with thrombospondin motifs (ADAMTS)-4, ADAMTS-5, matrix metalloproteinase (MMP)-1 and MMP-3 - but sensitivity and specificity was not reported [54]. The diagnostic performance of the two-step algorithm herein improves significantly on other current candidate biomarkers proposed for early-stage arthritis [16, 55, 56]. …”
Section: Discussionmentioning
confidence: 94%
“…Other serum markers for eOA detection have been suggested - disintegrin and metalloproteinase with thrombospondin motifs (ADAMTS)-4, ADAMTS-5, matrix metalloproteinase (MMP)-1 and MMP-3 - but sensitivity and specificity was not reported [54]. The diagnostic performance of the two-step algorithm herein improves significantly on other current candidate biomarkers proposed for early-stage arthritis [16, 55, 56]. …”
Section: Discussionmentioning
confidence: 94%
“…Specifically, it was recently shown that in models of the inflammatory disease of osteoarthritis, HDAC inhibition (HDACi) reduced symptoms by directly increasing acetylation of Nrf2 and histone H3 [63]. These changes occurred in parallel with a decrease in inflammatory markers such as IL-6 and TNFα, potentially via direct transcriptional regulation.…”
Section: Epigenetics and Redox Dependent Metabolic Regulationmentioning
confidence: 99%
“…Researchers have identified a number of risk factors for the worsening of knee OA symptoms and structure, such as age, ethnicity and malalignment 3, 4 , however modifiable risk factors are required to prevent progression to advanced disease and/or surgery. To date, the strongest known modifiable risk factors for worsening of knee pain in people with knee OA are a higher body mass index (BMI) and infrapatellar fat pad or intercondylar synovitis 4 , whilst a recent meta-analysis identified greater knee pain at baseline as the only modifiable risk factor associated with structural progression 3 .…”
mentioning
confidence: 99%